Bibliometric Analysis of Community Acceptance towards Reusable Diapers - Abadi, Totok Wahyu (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This research aims to elucidate the development of studies on public acceptance of reusable diapers and their relevance. A quantitative descriptive approach and bibliometric analysis were employed to achieve this objective. Data were collected from Semantic Scholar, Crossref, and Google Scholar. The collected articles were subsequently processed and analyzed using VOSviewer. The research results reveal that four primary topics are pertinent to society’s acceptance of reusable diapers: societal behavior and acceptance of disposable diapers and measures to address diaper rash; causes of diaper rash in newborns and the severity index of dermatitis; prevention of diaper rash in infants through personal hygiene practices; and the risks associated with diaper use in toddlers. The transition from disposable to reusable diapers is crucial due to its significant environmental and health benefits, particularly in reducing the incidence of diaper rash. The study implies further research on mothers’ acceptance of reusable diapers in Indonesia, encompassing knowledge, attitudes, and behaviors.